Echocardiographic parameters to identify sickle cell patients with cardio‐pathology. Issue 9 (14th May 2018) - Chiadika, Simbo; Lim‐Fung, Mary; Llanos‐Chea, Fiorella; Serauto Canache, Astrid; Yang, Wei; Paruthi, Christina; Zhang, Xu; McPherson, David D.; Idowu, Modupe
Abstract : Background: Sickle cell disease (SCD) affects millions of people and causes chronic hemolytic anemia leading to vasculopathies such as pulmonary hypertension and abnormalities in cardiac function that increase complications and mortality. It is therefore crucial to identify cardiac abnormalities in SCD. We aimed to assess the prevalence of echocardiographic parameters in SCD to help identify cardiopulmonary risk. Methods: Ninety‐one patients (53% male), median age of 30, body surface area (BSA) of 1.79 m 2, hemoglobin of 8.8 g/dL, and creatinine of 0.7 mg/dL identified. We retrospectively measured laboratory and echocardiographic parameters in patients with SCD : left ventricular (LV) dimensions, LV ejection fraction (LVEF), LV Myocardial Performance Index (MPI), LV Mass Index (MI), Left Atrial Volume Index (LAVI), Tricuspid Regurgitation Velocity (TRV), tricuspid annular plane systolic excursion (TAPSE), right heart dimensions. Results: Prevalence of left heart abnormalities was 32%: increased LV end‐diastolic diameter (EDD), 78%: LV MPI, 21%: diastolic dysfunction, 38%: decreased LVEF, 24%: increased LVMI, and 47%: increased LAVI. Right heart abnormalities were 39%: TAPSE, 38%: increased TRV, and 59%: increased pulmonary systolic pressure (PASP). Multivariate logistic regression analysis was significant for increased LVMI and LAVI in those with hemoglobin ≤8 g/dL (odds ratio (OR) 7.4, 95% confidence interval (CI) 2.23–24.6, P  = .001) and (OR 3.32, 95% CI 1.18–9.33, P  = .023). Conclusions: We confirmed increased prevalence of abnormal LVEDD, LVMI, diastolic function, LAVI, and PASP in SCD. In addition, we identified abnormal LV MPI (78%), TAPSE (29%). These parameters may be useful and readily accessible echocardiographic prognostic tools in this population.